Application potential of biomarkers in periodic dental screening protocol for patients working in harmful conditions - Sydorenko, O. O.; Sydorenko, A. Yul.; Voznyi, O. V.; Pavlov, S. V.; Zbarakh, O. O.; Сидоренко, Олександр Олександрович; Сидоренко, Анна Юліївна; Возний, Олександр Вікторович; Павлов, Сергій Васильович; Zbarakh, O. O. (publishing center of the ESCBM, The Czech Republic, 2018)
The problem of dental diseases prevention is rather actual, since the results of numerous researches demonstrate that the incidence of the major dental diseases is really high. Due to this, essential preventive protocols have been elaborated which allows prevention of future nosological illnesses. The main criteria in the modern preventive stomatology are the ratio between time that is necessary for a dentist to prevent a disease, benefits of the measures undertaken according to the given prevention protocol, and risks of untimely prevention. All these factors can be minimized, and effective results of nosological disorders prevention can be obtained.
Keywords: тези доповідей; vitamin D-binding protein; biomarkers; lactoferrin; vitamin D; prosthetic rehabilitation